1970
DOI: 10.1088/0022-3727/3/3/309
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of zirconates and stannates with the pyrochlore structure

Abstract: The properties of the stannates and zirconates (M2Sn2O7 and M2Zr2O7) of yttrium, lanthanum, cerium and neodymium are discussed, and the materials are considered for possible application in magnetohydrodynamic (MHD) power generation. Measurements are discussed of their structural properties, thermal expansion, thermal diffusivity, electrical resistivity, resistance to oxidation, to chemical corrosion, and to electrolytic corrosion. Thermal shock resistance is also qualitatively assessed. For non-electrical appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Pyrochlores, depending on their compositions, 31,33 can either be ionic or MIEC. Zirconates of Nd, Gd, and Y showed electrical conductivity independent of P (O 2 ) at different oxygen partial pressures 34,35 . In the present work, the electrical conductivity of (Gd 1− x Eu x ) 2 Zr 2 O 7 is reported in the oxygen partial pressure range, e.g., 1.0 × 10 −4 to 1.0 atm at temperatures of 673–873 K. Figure 9 shows the electrical conductivity of (Gd 0.4 Eu 0.6 ) 2 Zr 2 O 7 as a function of oxygen partial pressure P (O 2 ) at different temperatures.…”
Section: Resultsmentioning
confidence: 57%
“…Pyrochlores, depending on their compositions, 31,33 can either be ionic or MIEC. Zirconates of Nd, Gd, and Y showed electrical conductivity independent of P (O 2 ) at different oxygen partial pressures 34,35 . In the present work, the electrical conductivity of (Gd 1− x Eu x ) 2 Zr 2 O 7 is reported in the oxygen partial pressure range, e.g., 1.0 × 10 −4 to 1.0 atm at temperatures of 673–873 K. Figure 9 shows the electrical conductivity of (Gd 0.4 Eu 0.6 ) 2 Zr 2 O 7 as a function of oxygen partial pressure P (O 2 ) at different temperatures.…”
Section: Resultsmentioning
confidence: 57%
“…21 On the other hand, zirconates of Nd, Gd, and Y showed only ionic conductivity under varied oxygen partial pressures. 22,23 It was found that if there is a possibility of forming more than one valance state, the chance of electronic conduction arises. 24 Abrantes et al 20 showed that for Yb 2 Ti 2 O 7 pyrochlore above 700 C the electronic contribution to the total electrical conductivity increased only under highly reducing conditions.…”
Section: A Ionic Conductivitymentioning
confidence: 99%
“…Zirconate pyrochlores, with the chemical formula A 2 Zr 2 O 7 (where A is a rare earth element), have attracted considerable attention because of their potential use as solid oxide fuel cell electrode materials, fluorescence screens, thermal-barrier coatings, high-temperature heating elements, oxidation catalysts, and refractory ceramic materials for use in magnetohydrodynamic power generation [1][2][3][4][5][6][7][8]. Because they exhibit remarkable resistance to structural amorphization under ion-beam irradiation [6] and high chemical durability (release rates typically <10 À5 g m À2 d À1 based on zirconium) [9], as well as the fact that zirconium has a low neutron absorption cross-section [7], zirconate pyrochlores have also been proposed as inert matrix materials for actinide burning [7,9] and host matrices for high level radioactive waste, especially for long half-life actinides [10].…”
Section: Introductionmentioning
confidence: 99%